Antiphospholipid syndrome: an update. (24th April 2015) - Merashli, Mira; Noureldine, Mohammad Hassan A.; Uthman, Imad; Khamashta, Munther
Abstract Background Antiphospholipid syndrome (APS) or 'Hughes syndrome' is a prothrombotic disease characterized by thrombosis and pregnancy morbidity in the presence of antiphospholipid antibodies (aPL). More than three decades have passed, and experts are still uncovering new pieces of this disease complex pathogenesis and management. Materials and methods We searched in literature using MEDLINE and PubMed databases focusing on the latest development on disease pathogenesis, risk assessment of thrombosis and treatment of APS. Results The phosphatidylinositol 3‐kinase (PI3K)–AKT‐mTORC pathway was most recently identified to have a crucial role in activating inflammation among endothelial vessel wall causing vascular lesions in APS. Additionally, new variables are being implemented to assess the risk of thrombosis in patients with APS. Global APS Score (GAPSS) utilizes cardiovascular risk factors and new autoimmune antibodies as part of the score assessment and is the most valid so far. It can be a promising tool in the future for prediction of thrombosis. Anticoagulation remains the cornerstone in APS; however, many new potential therapeutic agents are developing and are currently under investigation. Conclusions The most recent advances in pathogenesis, risk stratification and treatment provide a platform for high yield studies with the ultimate goal of providing the optimal management to patients with APS.